Hasil dan Motivasi Belajar Siswa Mata Pelajaran IPS Melalui Metode Kooperatif Tipe Modelling The Way - Jira (IAIN PAREPARE, 2019)
This research was conducted in two cycles, namely cycle I which was held 2 times and cycle II which was also held as much as 2 meetings. This research was conducted for 3 months and supplemented by summarizing all existing research results. The result is an increase in student learning in Class V SDN 30 Parepare through the cooperative learning model Modeling The Way is (i) in the first cycle, including the medium category with an average value of 66.25 while in the second cycle progressing with a very high category with an average value - average 78,13, (ii) there was an increase in the learning outcomes of Class V students of SDN 30 Parepare through the Modeling the Way cooperative learning model, both qualitatively and quantitatively. So this model is considered quite effective in teaching, especially in the field of social studies at elementary school level, because it can improve student learning outcomes, both in doing their assignments at school and trying to provide opportunities for students to do and try in each of their learning activities.